Simulation model of load balancing in distributed computing systems; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Botygin I. A. Igor Aleksandrovich (Information technologies in Mechanical Engineering, 2017)
Title screen